2015
DOI: 10.3889/oamjms.2015.068
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Mental Health Status of Undergraduate Medical Trainees in the University of Calabar, Nigeria: A Cross-Sectional Study

Abstract: BACKGROUND:The mental health status of medical students has been proven to be poor compared to their peers in other disciplines and has led to grave personal and professional consequences. This subject has however remained largely unexplored in our medical school.AIM:The study was therefore conducted to assess the prevalence of mental health of medical students in the University of Calabar, Cross river state, Nigeria.METHODOLOGY:A descriptive cross-sectional survey of 451 randomly selected medical students fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
(41 reference statements)
5
10
0
1
Order By: Relevance
“…The mental health status of medical trainees has long been recognized as a cause for concern in both developed and developing countries [11][12][13][14]. The mean age of the respondents was consistent with similar studies carried out in medical schools [15][16][17][18], in which the mean age was 22.2 ± 2.149 and majority of the students were between the ages 19-31 years. Overall, two out of three of the respondents were female, this is quite different from what was obtained in a study conducted in Japan which reported that 66.3% were male and 33.7% were female [19].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The mental health status of medical trainees has long been recognized as a cause for concern in both developed and developing countries [11][12][13][14]. The mean age of the respondents was consistent with similar studies carried out in medical schools [15][16][17][18], in which the mean age was 22.2 ± 2.149 and majority of the students were between the ages 19-31 years. Overall, two out of three of the respondents were female, this is quite different from what was obtained in a study conducted in Japan which reported that 66.3% were male and 33.7% were female [19].…”
Section: Discussionsupporting
confidence: 82%
“…Assessment of psychological morbidity or mental health status of the respondents using the GHQ12 was a key finding in this study. The prevalence of psychological morbidity was 66.76%.This was found to be high compared to other studies [18,19,22,23]. However, studies conducted among medical students in Australia, England and Malaysia, which used the same cut off as the present study, showed comparable results as observed in the present study [14,24,25] Table 2.…”
Section: Mental Health Statussupporting
confidence: 77%
“…reported that 39.2% of medical student in Calabar had poor mental health [ 13 ]. Previous research has identified long hours of study, and the impositions of emotional burden [ 14 ], high workload [ 15 ] and considerable financial pressure as the principal stressors. Omigbodun et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from Nigeria linked higher stress levels amongst undergraduate medical students to inadequate educational resources, family pressure and financial difficulties but did not discuss attrition rates [ 43 , 44 ]. Medical graduates interviewed in a South African study also noted the impact that exams and patient exposure had on them emotionally, and the need for support mechanisms, but did not comment on attrition rates either [ 22 ].…”
Section: Discussionmentioning
confidence: 99%